Inovasi Kurikulum Al-Qur'an Hadist Dalam Meningkatkan Kualitas Pembelajaran di MTs Sunan Kalijaga Tulung, Klaten - Mahmudah, Mia Rosiana; Muh Wasith Achadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of curriculum innovation in Al-Qur’an Hadith learning at MTs Sunan Kalijaga Tulung, Klaten, which includes the stages of planning, implementation, evaluation, supporting and inhibiting factors, as well as its implications for improving the quality of learning. This research uses a qualitative approach with a case study and phenomenological design. The research subjects consisted of Al-Qur’an Hadith teachers and the madrasah principal who were selected using purposive sampling techniques. Data collection techniques were carried out through in-depth interviews, non-participant observation, and documentation, while data analysis used the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of curriculum innovation at MTs Sunan Kalijaga has been directed toward the Merdeka Curriculum with the support of the madrasah curriculum development team. At the planning stage, teachers formulate learning outcomes from general objectives to more specific objectives. At the implementation stage, teachers use discussion methods, problem solving, worship practices, project-based learning, group work, and the use of digital media. Evaluation is conducted through pre-tests, post-tests, affective observation, joint daily assessments, and structured examinations. Supporting factors include teacher training, support from the madrasah principal, and supervision from educational supervisors, while the main inhibiting factor is the limited access to technology among students. The implementation of this curriculum innovation has a positive impact on improving discipline, religious character, ethics, and students’ active involvement in learning. Penelitian ini bertujuan untuk menganalisis implementasi inovasi kurikulum dalam pembelajaran Al-Qur'an Hadits di MTs Sunan Kalijaga Tulung, Klaten, yang meliputi tahapan perencanaan, implementasi, evaluasi, faktor pendukung dan penghambat, serta implikasinya terhadap peningkatan kualitas pembelajaran. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus dan fenomenologi. Subjek penelitian terdiri dari guru Al-Qur'an Hadits dan kepala madrasah yang dipilih menggunakan teknik purposive sampling. Teknik pengumpulan data dilakukan melalui wawancara mendalam, observasi non-partisipan, dan dokumentasi, sedangkan analisis data menggunakan model interaktif Miles dan Huberman, yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi inovasi kurikulum di MTs Sunan Kalijaga telah diarahkan pada Kurikulum Merdeka dengan dukungan tim pengembangan kurikulum madrasah. Pada tahap perencanaan, guru merumuskan hasil pembelajaran dari tujuan umum ke tujuan yang lebih spesifik. Pada tahap implementasi, guru menggunakan metode diskusi, pemecahan masalah, praktik ibadah, pembelajaran berbasis proyek, kerja kelompok, dan penggunaan media digital. Evaluasi dilakukan melalui pre-test, post-test, observasi afektif, penilaian harian bersama, dan ujian terstruktur. Faktor pendukung meliputi pelatihan guru, dukungan dari kepala madrasah, dan pengawasan dari pengawas pendidikan, sedangkan faktor penghambat utama adalah terbatasnya akses teknologi di kalangan siswa. Implementasi inovasi kurikulum ini berdampak positif pada peningkatan disiplin, karakter religius, etika, dan keterlibatan aktif siswa dalam belajar.